Effect of tissue thickness and liquid composition on the penetration of long-lifetime reactive oxygen and nitrogen species (RONS) generated by a plasma jet. (2nd August 2018) - Nie, L; Yang, Y; Duan, J; Sun, F; Lu, X; He, G
Abstract: Two of the key questions in plasma medicine are how deep the reactive oxygen and nitrogen species (RONS) generated by a plasma can penetrate into tissue and how the liquid (extracellular and intracellular fluid) composition affects the concentration of RONS. In this paper, different thicknesses of pig muscle tissue are used as a tissue mode to investigate the effect of tissue thickness on the penetration of RONS through tissue. Six different types of liquid (inorganic group: double-distilled water (DDW), 1% phosphate-buffered saline, 0.9% NaCl; organic group: 5% glucose, 2% serum and 10% serum solution) are used in the receiving chamber under the tissue in order to try to understand the effect of liquid composition on the penetration of RONS (H2 O2, and ) generated by the plasma. It is found that when a tissue thickness of 500 µ m is used the H2 O2 concentrations in organic liquids are about 20–30 times higher than in DDW. The and concentrations in serum liquid are much higher than in all other liquids, which might be due to the plasma reacting with amino acids and proteins. Besides, the concentration in organic solution is higher than the concentration for the same experimental conditions. Furthermore, when the serum percentage is increased from 2% to 10%, the concentration increases dramatically but the concentration decreases significantly. This is especially true for a tissue thickness of 500 µ m. One novel discovery is the RONS do not only penetrate the tissue by diffusion—there are also reactions between the plasma and the liquid which affect the final RONS concentration.